Does Infertility Stress Impair Sexual Function in Infertile Women and Men? A Cross-Sectional Study in Iran - Amraei, Samira; Abedi, Parvin; Nikbakht, Roshan; Tadayon, Mitra; Maraghi, Elham (Frontiers in Medicine, 2022)
Background: Infertility is one of the challenging issues worldwide which is estimated to affect around 50 million couples. This study aimed to evaluate the relationship between infertility stress and sexual function in infertile women and men. Methods: In this cross-sectional study, 300 infertile women and men were recruited. A demographic questionnaire, the Fertility Problem Inventory, the Female Sexual Function Scale (FSFI), and the International Index of Erectile Function (IIEF) were used to collect data. Independent t-test, Chi-square, and linear and logistic regressions were used to assess the data. Results: The total score of sexual function in women and men was 22.18±7.86 and 57.7±17.8, respectively. Infertility duration and the ability to pay for the costs of infertility treatment had a significant relationship with sexual function in women. A significant association was found between communication concerns and sexual function score in infertile men. Infertile women had more sexual concerns, while infertile men had more communication concerns. Conclusion: This study showed that infertile women had more infertility stress than infertile men. Women with higher infertility duration and inability to pay for the infertility treatment costs had impaired sexual function. Infertile women had more sexual concerns, while infertile men had more communication concerns. Policy makers need to consider strategies such as counseling for infertile men and women to help them cope with their problems, especially their psychological problems. Lack of random enrollment of participants and lack of control group were the limitations of this study.